ナンキョク エンガン ブ オヨビ カタバ フウタイ ノ セキセツ リョウ ノ ヘンカ 1979・80 ネン ノ ショウワ キチ ミズホ キチ ノ カンソク - 和田, 誠; ワダ, マコト; Wada, Makoto (1985)
P(論文) 南極域気水圏観測(POLEX-South)の期間(1979-1981年), 沿岸基地である昭和基地と内陸に位置しカタバ風帯のみずほ基地との気象・雪氷観測から, 両基地の積雪量と気象要素(雲量, 雪日数, 可降水量, ブリザード日数, 気圧の分散値)との関係について解析を行った。積雪量は昭和基地では, 夏季後半, 冬季および10月に増加を示した。一方みずほ基地では, 夏季後半, 冬季に増加している。夏季後半の増加は, 可降水量が夏に多いことが主な原因であり, 冬季の増加は, 強い低気圧の接近が主な原因となっている。また10月の昭和基地での増加は, 可降水量, 低気圧の両方の影響のためと考えられる。可降水量は夏と冬で大きな違いがあるため, 特にみずほ基地では, 夏に積雪量の増加が著しい。 The snow accumulation at Syowa and Mizuho Stations was recorded from the observations during the POLEX-South period and the monthly and seasonal variations of it were discussed using the data of the cloud amount, the number of days with snowfall, precipitable water, the number of days with blizzard and the pressure-variance. The accumulation generally increased in late summer, winter and October at Syowa Station, and in late summer and winter at Mizuho Station. Its increase in late summer relies on the content of precipitable water and the increase in winter depends on the cyclones that approached the region. The increase in October at Syowa Station relies on the both factors. There is a large difference in the content of precipitable water between summer and winter, so the summer season plays an important role in snow accumulation at Mizuho Station rather than the winter season. departmental bulletin paper